2001
DOI: 10.1074/jbc.m106839200
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein Secretion and Triglyceride Stores in the Heart

Abstract: The genes for apolipoprotein B and microsomal triglyceride transfer protein are expressed in mouse and human heart tissue. Why the heart would express these "lipoprotein assembly" genes has been unclear. Here we demonstrate that the beating mouse heart actually secretes spherical lipoproteins. Moreover, increased cardiac production of lipoproteins (e.g., in mice that express a human apolipoprotein B transgene) was associated with increased triglyceride secretion from the heart and decreased stores of triglycer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
58
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(65 citation statements)
references
References 40 publications
7
58
0
Order By: Relevance
“…Because HuB/hLpL GPI hearts secrete more apoB, it is likely that this transgene increased lipid removal from the heart. This conclusion is supported by studies that showed a reduction in heart lipid due to apoB expression in long chain acyl CoA dehydrogenase knockout mice (10). In addition, these investigators found that cardiacspecific loss of microsomal triglyceride transfer protein, leading to an inability to produce lipoproteins in the heart, increased cardiac triglyceride stores.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Because HuB/hLpL GPI hearts secrete more apoB, it is likely that this transgene increased lipid removal from the heart. This conclusion is supported by studies that showed a reduction in heart lipid due to apoB expression in long chain acyl CoA dehydrogenase knockout mice (10). In addition, these investigators found that cardiacspecific loss of microsomal triglyceride transfer protein, leading to an inability to produce lipoproteins in the heart, increased cardiac triglyceride stores.…”
Section: Discussionsupporting
confidence: 73%
“…Hearts synthesized and secreted lipoproteins (8). Cardiac apoB expression led to reduced heart lipids after induction of diabetes in mice (9) and in the presence of long chain acyl coA dehydrogenase deficiency (10). This supported the hypothesis that heart apoB enables the heart to secrete excess lipid in lipoproteins (8).…”
supporting
confidence: 67%
“…In contrast, 3 H oleate specific activity was not different in coronary sinus and arterial plasma (P ϭ 0.17). There was a strong negative correlation between 14 C oleate fractional extraction (34 Ϯ 5%) and plasma oleate concentration (R ϭ 0.973, P Ͻ 0.01, data not shown).…”
Section: Resultsmentioning
confidence: 90%
“…Coronary sinus concentrations of both oleate and total FFA were significantly lower than arterial (P Ͻ 0.001). Coronary sinus 14 C oleate specific activities were also lower than arterial (P ϭ 0.033). In contrast, 3 H oleate specific activity was not different in coronary sinus and arterial plasma (P ϭ 0.17).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation